Genome-wide identification of the rice calcium-dependent protein kinase and its closely related kinase gene families: Comprehensive analysis of the CDPKs gene family in rice [Oryza sativa] - Asano, T.(National Inst. of Agrobiological Sciences, Tsukuba, Ibaraki (Japan)); Tanaka, N; Yang, G; Hayashi, N; Komatsu, S (Plant and cell physiology, 2005)
In plants, calcium acts as a universal second messenger in various signal transduction pathways. The plant-specific calcium-dependent protein kinases (CDPKs) play important roles regulating downstream components of calcium signaling. We conducted a genome-wide analysis of rice CDPKs and identified 29 CDPK genes and eight closely related kinase genes, including five CDPK-related kinases (CRKs), one calcium and calmodulin-dependent protein kinase (CCaMK) and two phosphoenolpyruvate (PEP) carboxylase kinase-related kinases (PEPRKs) The mRNA splicing sites of the rice CDPKs, CRKS and PEPRKS (but not OSCCaMK) are highly conserved, suggesting that these kinases are derived from a common ancestor. RNA gel blot analyses revealed that the majority of rice CDPK genes exhibited tissue-specific expression. Expression of OsCPK9 was elevated in seedlings infected by rice blast, indicating that this gene plays an important role in signaling in response to rice blast treatment. Our genomic and bioinformatic analyses will provide an important foundation for further functional dissection of the rice CDPK gene family.